Republic of Poland : Financial Sector Assessment Program-Technical Note-Insurance Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2019)
This Technical Note on Insurance Sector Regulation and Supervision provides an update and an assessment of the development of regulation and supervision of the Polish insurance sector since an assessment concluded in 2012. The note focuses on key issues, with reference to international standards but without presenting a detailed assessment of Poland's observance. The supervision of intermediaries has also been strengthened in line with a 2012 Financial Sector Assessment Program recommendation. The Solvency II changes appear well-embedded, without significant exemptions or transitional arrangements. With limited long-term guarantee business, life insurers have currently no need for the special measures adopted for such business in many EU countries. However, the recent emergence of the first Polish financial conglomerate, which is headed by an insurer, poses supervisory challenges. In respect to the selected other areas of the insurance framework that were reviewed, the findings highlighted strengths in the approach, with some scope for further development.